Differential response of the soil nutrients, soil bacterial community structure and metabolic functions to different risk areas in Lead-Zine tailings - Liu, Zexun; Zhuang, Jiayao; Zheng, Kang; Luo, Chengcheng (Frontiers in Microbiology, 2023)
Rapid growth in the mining industry has brought about a large formation of tailings, which result in serious destruction of the ecological environment and severe soil pollution problems. This study assesses soil nutrients, soil bacterial community and soil microbes' metabolic function in heavily polluted areas (W1), moderately polluted areas (W2), lightly polluted areas (W3) and clean areas (CK) using 16S Illumina sequencing. The results of this study showed that compared with CK, a severe loss of soil nutrients and richness of OTUs (Chao1 and ACE indices) were observed with the aggravated pollution of tailings. The Chao1 and ACE indices in the W1 group decreased significantly by 15.53% and 16.03% respectively (P < 0.01). Besides, the relative abundance of Actinobacteria and Proteobacteria was high whereas and relative abundance of Chloroflexi in the polluted areas. Among them, W1 groups increased significantly the relative abundance of Actinobacteria and decreased significantly the relative abundance of Chloroflexi, these can be used as indicator phyla for changes in soil community structures under polluted stress. Tax4 Fun analysis showed that W1 groups affected the soil bacterial community and altered the primary types of biological metabolism in polluted areas. Tailings have adverse impacts on soil bacterial community and metabolic functions, and the deterioration in soil quality is dependent on the levels of tailings pollution. Cumulatively, this study provides valuable information on the bacterial community structure and metabolic functions in the tailing polluted soil.